2002
DOI: 10.1021/jf020800o
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-Release NPK Fertilizer Encapsulated by Polymeric Membranes

Abstract: The commercial granular fertilizer NPK6-20-30 was coated using polysulfone (PSF), polyacrylonitrile (PAN), and cellulose acetate (CA). The coatings were formed from the polymer solutions by the phase inversion technique. Measurements of the thickness and porosity of the prepared coatings and a microphotographic observation of the coatings were performed. The physical properties of the coatings influence the release rate of macronutrients which are present in the core of the coated fertilizer. In the case of PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
2
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(152 citation statements)
references
References 8 publications
6
127
2
7
Order By: Relevance
“…Corroborating Jarosiewicz and Tomaszewska (2003), the study by Chagas et al (2016) reported that higher phosphorus accumulation in onion bulb was obtained with the use of polymer-coated triple superphosphate. The source KIM COAT (LGP) presented no difference compared to conventional MAP.…”
Section: Phosphorus Contentmentioning
confidence: 89%
See 1 more Smart Citation
“…Corroborating Jarosiewicz and Tomaszewska (2003), the study by Chagas et al (2016) reported that higher phosphorus accumulation in onion bulb was obtained with the use of polymer-coated triple superphosphate. The source KIM COAT (LGP) presented no difference compared to conventional MAP.…”
Section: Phosphorus Contentmentioning
confidence: 89%
“…Gazola et al (2013) points out that in the case of phosphorus, a simple practice such as liming would be effective in reducing its problem of high soil adsorption and slow release fertilizer would not be required for this nutrient. For Jarosiewicz and Tomaszewska (2003) the efficacy of coated fertilizers relies on the solubility of the polymer that coats the granules. Moreover, the thickness and chemical nature of the coating resin, number of surface microcracks and fertilizer granule size determine the rate of nutrient release over time (Girardi and Mourão Filho, 2003).…”
Section: Phosphorus Contentmentioning
confidence: 99%
“…Isto irá regular o processo de fornecimento dos nutrientes. Essas taxas de liberação e de dissolução de fertilizantes solúveis em água dependem dos materiais de revestimento (Jarosiewicz & Tomaszewska, 2003). Ainda, segundo estes autores, a liberação do nutriente irá depender da temperatura e da umidade do solo.…”
Section: Tratamentos Icfunclassified
“…The first one involves the mechanism of progressive dissolution to attain slow nutrient release, which can be achieved by synthesising novel compounds with low water solubility (Bhattacharya et al 2007;Bandyopadhyay et al 2008). The second option is to coat the fertilizers with organic materials that have low water solubility (Jarosiewicz and Tomaszewska 2002;Ni et al 2010). The coating allows control over the rate of nutrient release by means of its diffusibility and biodegradability characteristics, depending on the varying physical and chemical properties of the coating material.…”
Section: Introductionmentioning
confidence: 99%